Desenvolvimento e caracterização de filmes poliméricos de amido de milho com incorporação de fibras de bagaço de cevada - Castanho, Maria Natalia (Universidade Federal de São Carlos, 2020)
Interest in the use of starch for biodegradable films is growing due to being a natural, renewable, abundant and low cost source. However, starch films generally have low values of mechanical properties. Thus, this work uses barley bagasse, a residue from the brewing industry, as a reinforcement option for corn starch films, maintaining the biodegradability property. For this purpose, starch films were developed with incorporation of 1 to 5% of barley bagasse fibers in three different particle sizes (35, 60 and 100 mesh). To obtain the films was used a microwave apparatus for heating and, subsequently, cast by casting. Mechanical tensile tests, scanning electron microscopy (SEM) in fractured samples, dynamic mechanical-thermal analysis (DMTA), thermogravimetric analysis (TGA) and derivative (DTG), differential exploratory calorimetry (DSC), Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (DRX), contact angle, biodegradation and toxicity tests were performed. In the tensile tests, the best results were for the films containing 2.5% barley with 35 mesh grain size and the film containing 1% barley with 100 mesh grain size, with tensile strength of 0.94 and 0.88 MPa and deformation 14,13 and 23.54%, when compared with barley film without added barley. DMTA analyzes determined the glass transition temperature of the films at approximately -46.7°C (± 1.8°C). Thermal analysis revealed that the addition of barley bagasse affected the thermal stability of the films. The contact angle test revealed hydrophilic character for the films. For the films used in the biodegradation test it was possible to observe higher CO2 emissions for the films containing barley, due to the higher carbon presence in these films.
Development and characterization of polymeric corn starch films incorporating barley bagasse fibers
Keywords: Filmes poliméricos; Filmes biodegradáveis; Amido de milho; Bagaço de cevada; Polymeric films; Biodegradable films; Corn starch; Barley bagasse; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::MATERIAIS NAO METALICOS::POLIMEROS, APLICACOES